Policy by Design : Inclusive Instructional Models for Advancing Neurodiversity Equity in Public Programs - Yinka Samuel Ogunlana; Amina Catherine Peter-Anyebe (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
This review explores the inquiry of policy-informed instructional models and their implications for advancing neurodiversity equity in public programs. Rather than assuming positive outcomes, it critically examines whether policy frameworks support or constrain inclusive practices. Literature indicates that policies can restrict teacher autonomy through rigid compliance mechanisms, yet may enhance equity when aligned with frameworks such as Universal Design for Learning (UDL). Neurodiversity scholarship highlights the necessity of inclusive, flexible, and context-sensitive approaches that respond to diverse cognitive profiles. By synthesizing perspectives across education, disability studies, and policy analysis, this paper identifies tensions, opportunities, and gaps in current instructional models. The goal is to provide a nuanced understanding of how policy and pedagogy intersect in shaping equitable outcomes for neurodiverse learners, allowing themes to emerge organically from the evidence.